Tata Kelola dan Manajamen Dana Abadi (Endowment Fund) Perguruan Tinggi : Sebuah Tinjauan Literatur Sistematis - Samir, Salman; Kwan, Kwandou Wirawan; Rizky, Utamy; Andi, Iqra Pradipta Nasir; Samintang, Samintang (Universitas Negeri Padang, 2024)
Over the last 2 decades, Indonesia has brought about many reforms in the world of education, especially universities which have a strategic role in building quality human resources. One important aspect in supporting the university is the funding aspect. One source of funding currently being worked on by Indonesia is an endowment fund. D An endowment fund is a financial asset provided by an institution or organization that is intended for college expenditure. The endowment fund has a very good role for the sustainability of the campus, therefore the endowment needs to be managed effectively and efficiently. The purpose of this research is to identify what aspects can support the effective and efficient management of endowment funds in universities. The method used to answer the research objectives is to use a Systematic Literature Review. As a result of our Systematic Literature Review, there are 8 aspects that support efficient endowment management. Such as synergy of alumni and universities, presenting professional staff to manage endowments, improving institutional aspects of the university, contributing collectively, promoting endowments, providing long-term plans for endowment allocations, Increasing the role of stakeholders, uphold transparency and accountability, and provide information for potential donors